2022
DOI: 10.1007/s00246-022-02972-3
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of Cardiac Function Following Multisystem Inflammatory Syndrome in Children Associated with COVID-19

Abstract: Multisystem inflammatory syndrome in children (MIS-C) after COVID-19 is commonly associated with cardiac involvement. Studies found myocardial dysfunction, as measured by decreased ejection fraction and abnormal strain, to be common early in illness. However, there is limited data on longitudinal cardiac outcomes. We aim to describe the evolution of cardiac findings in pediatric MIS-C from acute illness through at least 2-month follow-up. A retrospective single-center review of 36 patients admitted with MIS-C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
3
12
0
Order By: Relevance
“…Abnormal strain measurements with preserved LVEF, during the acute phase of MIS-C and in different follow-up periods, have been also described in previous studies [ 4 , 17 , 23 , 41 ]. The above findings are suggestive of subclinical myocardial injury, that can be recognized with STE with LV-GLS analysis, but not with conventional echocardiographic parameters like the LVEF [ 11 ].…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Abnormal strain measurements with preserved LVEF, during the acute phase of MIS-C and in different follow-up periods, have been also described in previous studies [ 4 , 17 , 23 , 41 ]. The above findings are suggestive of subclinical myocardial injury, that can be recognized with STE with LV-GLS analysis, but not with conventional echocardiographic parameters like the LVEF [ 11 ].…”
Section: Resultssupporting
confidence: 75%
“…Specifically, we found that during the acute phase, LV-GLS was impaired in 42.9% of the patients, while LVEF was normal in all but one of these patients. In MIS-C, LV dysfunction, identified by LV-GLS, during the acute illness, has been reported in other studies, where the rate of GLS impairment was estimated at 44–65% [ 23 , 40 ]. Study data from mid-term echocardiographic follow-up evaluation (approximately at 2 months), report that while LV-GLS was improved in most patients, there was a persistence of GLS abnormalities in 21–24% of MIS-C patients [ 10 , 23 ].…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Abnormal strain measurements with preserved LVEF, during the acute phase of MIS-C and in different follow-up periods, have been also described in previous studies [4,17,23,37]. The above ndings are suggestive of subclinical myocardial injury, that can be recognized with STE with LV-GLS analysis, but not with conventional echocardiographic parameters like the LVEF [11].…”
Section: Discussionsupporting
confidence: 68%
“…There were 206 publications that resulted with our keyword search on MIS-C and follow-up between 2020 and 2022. Eleven published studies fit the inclusion criteria with a total of 343 participants (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). All studies included patients who met criteria for MIS-C per the CDC guidelines (see Figure 1).…”
Section: Yield Of the Searchmentioning
confidence: 99%